Greek Literature. (25th March 2015) - Unknown
Abstract : When I started writing these reviews I presaged aggravated grumpiness in reaction to proliferating guides, handbooks and companions ( G&R 52 [2005], 250). Subsequent experience has disconfirmed that prediction. I am not quite megalomaniac enough to believe that my threat cowed editors into raising their standards, nor modest enough to believe that my own standards have been subverted by mere habituation. Perhaps, then, proliferation itself has raised standards by increasing competition. However that may be, the current crop illustrates two ways in which specimens of the genre can earn their keep. The Cambridge Companion to Greek Comedy achieves success by combining consistent excellence on the part of the contributors with a well-conceived and well-executed editorial plan. Martin Revermann's introduction is a model of how it should be done: he sets out the agenda (approaching the Greek comic tradition as a continuum, and moderating as far as possible the Aristophano-, Menandro-, and Athenocentricity of our evidence) and provides an overview, giving lucid summaries of individual chapters that also highlight their interconnections and their contributions to the overall structure ('Setting the Stage', 'Comic Theatre', 'Central Themes' 'Politics, Law and Social History', 'Reception'). Andreas Willi, on 'The Language(s) of Comedy', does an especially fine job on a difficult brief; I was also impressed by Ralph Rosen's thoughtful essay on the 'comic hero' (a category with which I feel uncomfortable). But, in singling out those two for mention, I do not mean to detract from the high quality sustained throughout.